2001
DOI: 10.1097/00005768-200112000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Creatine-dextrose and protein-dextrose induce similar strength gains during training

Abstract: We concluded that postexercise supplementation with PRO-CHO resulted in similar increases in strength after a resistance exercise training program as compared with CR-CHO. However, the greater gains in total mass for the CR-CHO group may have implications for sport-specific performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 32 publications
2
40
0
1
Order By: Relevance
“…Following a 28-day washout period, which is sufficient for muscle PCr concentration to return to basal level (24,39), subjects crossed over to consume the alternate supplement for 10 days. Four-day diet records were acquired from all subjects during the last 4 days of both treatments and were analyzed for daily total calorie and macronutrient composition using Nutritionist V (First Data Bank, San Bruno, CA) (86). FFM and body fat percentage were determined using dual-energy X-ray absorptiometry (QDR-1000W; Hologic, Waltham, MA) as previously described (86).…”
Section: Experimental Protocolmentioning
confidence: 99%
See 3 more Smart Citations
“…Following a 28-day washout period, which is sufficient for muscle PCr concentration to return to basal level (24,39), subjects crossed over to consume the alternate supplement for 10 days. Four-day diet records were acquired from all subjects during the last 4 days of both treatments and were analyzed for daily total calorie and macronutrient composition using Nutritionist V (First Data Bank, San Bruno, CA) (86). FFM and body fat percentage were determined using dual-energy X-ray absorptiometry (QDR-1000W; Hologic, Waltham, MA) as previously described (86).…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Four-day diet records were acquired from all subjects during the last 4 days of both treatments and were analyzed for daily total calorie and macronutrient composition using Nutritionist V (First Data Bank, San Bruno, CA) (86). FFM and body fat percentage were determined using dual-energy X-ray absorptiometry (QDR-1000W; Hologic, Waltham, MA) as previously described (86). Total body water was measured using bioelectric impedance analysis (BIA-101A; RJL Systems, Mt.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…Relatively small amounts of creatine are found in meat and fish and therefore supplementation provides a cost effective and simple means of increasing creatine availability without excessive fat, protein or calorific intake. Tarnopolsky et al compared 10 g creatine monohydrate and 50 g CHO against 10 g casein protein and 50 g CHO and reported that the creatine group reported a greater increase in fat free mass compared to the protein group [43]. The implications of this suggest that in sports where body weight is unimportant, creatine is a superior supplement than casein protein when combined with CHO to enhance hypertrophy.…”
Section: Creatinementioning
confidence: 99%